2009
DOI: 10.3892/ijmm_00000287
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and BBB damage induced by sera from patients with secondary progressive multiple sclerosis

Abstract: Abstract. An important component of the pathogenic process of multiple sclerosis (MS) is the blood-brain barrier (BBB) damage. We recently set an in vitro model of BBB, based on a three-cell-type co-culture system, in which rat neurons and astrocytes synergistically induce brain capillary endothelial cells to form a monolayer with permeability properties resembling those of the physiological BBB. Herein we report that the serum from patients with secondary progressive multiple sclerosis (SPMS) has a damaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has been reported that BBB disruption could be caused by gut microbiota dysbiosis, leading to the pathogenic antigen and serum protein leakage into CNS. This process has been previously demonstrated in the studies of schizophrenia, depression, Alzheimer’s disease (AD), Parkinson’s disease (PD) and MS, although the exact route is unclear [ 39 , 47 , 49 52 ].…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that BBB disruption could be caused by gut microbiota dysbiosis, leading to the pathogenic antigen and serum protein leakage into CNS. This process has been previously demonstrated in the studies of schizophrenia, depression, Alzheimer’s disease (AD), Parkinson’s disease (PD) and MS, although the exact route is unclear [ 39 , 47 , 49 52 ].…”
Section: Discussionmentioning
confidence: 95%